Bibliometrics in glass and other sciences: A Plea for reason. (15th May 2017) - Montazerian, Maziar; Zanotto, Edgar Dutra; Eckert, Hellmut
Abstract: We show a scientometric analysis for glass researchers and compare it with those for researchers in two fashionable research topics, representing the science‐push area "graphene" and the market‐pull area "lithium ion battery (LIB)". We also present similar statistics for two widely different macro fields, "materials science" (which contains the other three) and "mathematics". While productivity (number of published articles) of a researcher and his/her H ‐index are found to be correlated, these correlations are very different for different research fields, depending on their size, fragmentation, interdisciplinarity, and on the community's publication and citation culture. We also explore the correlation between citation statistics and scientific quality and find it to be elusive. While certain bibliometric indexes indeed indicate how active, prolific, and visible a researcher (or a research group) is, we argue that quality—evaluated by the originality, strength, reproducibility and relevance of the findings of a researcher's publications (as judged by peer review)—is much more important than the number of published articles and citations, and this is where efforts must be concentrated by researchers and evaluating bodies.